Mannose-binding lectin 2 gene polymorphisms and their association with tuberculosis in a Chinese population - Jun-Xian Zhang; Wen-Ping Gong; Dong-Lin Zhu; Hui-Ru An; You-Rong Yang; Yan Liang; Jie Wang; Jing Tang; Wei-guo Zhao; Xue-Qiong Wu (BMC, 2020)
Abstract Background Immune- and inflammation-related genes (IIRGs) play an important role in the pathogenesis of tuberculosis (TB). However, the relationship between IIRG polymorphisms and TB risk remains unknown. In this study, the gene polymorphisms and their association with tuberculosis were determined in a Chinese population. Methods We performed a case-control study involving 1016 patients with TB and 507 healthy controls of Han Chinese origin. Sixty-four single-nucleotide polymorphisms (SNPs) belonging to 18 IIRGs were genotyped by the PCR-MassArray assay, and the obtained data was analyzed with χ 2-test, Bonferroni correction, and unconditional logistic regression analysis. Results We observed significant differences in the allele frequency of LTA rs2229094*C (P = 0.015), MBL2 rs2099902*C (P = 0.001), MBL2 rs930507*G (P = 0.004), MBL2 rs10824793*G (P = 0.004), and IL12RB1 rs2305740*G (P = 0.040) between the TB and healthy groups. Increased TB risk was identified in the rs930507 G/G genotype (P adjusted  = 0.027) under a codominant genetic model as well as in the rs2099902 (C/T + C/C) vs T/T genotype (P adjusted  = 0.020), rs930507 (C/G + G/G) vs C/C genotype (P adjusted  = 0.027), and rs10824793 (G/A + G/G) vs A/A genotype (P adjusted  = 0.017) under a dominant genetic model after Bonferroni correction in the analysis of the overall TB group rather than the TB subgroups. Furthermore, the rs10824793_rs7916582*GT and rs10824793_rs7916582*GC haplotypes were significantly associated with increased TB risk (P = 0.001, odds ratio [OR] = 1.421, 95% confidence interval [CI]: 1.152-1.753; and P = 0.018, OR = 1.364, 95% CI: 1.055-1.765, respectively). Moreover, the rs10824793_rs7916582*AT/AT or rs10824793_rs7916582*GT/GT diplotype showed a protective (P = 0.003, OR = 0.530, 95% CI: 0.349-0.805) or harmful (P = 0.009, OR = 1.396, 95% CI: 1.087-1.793) effect against the development of TB. Conclusions This study indicated that MBL2 polymorphisms, haplotypes, and diplotypes were associated with TB susceptibility in the Han Chinese population. Additionally, larger sample size studies are needed to further confirm these findings in the future.